Pengembangan Time-Temperature Indicator Berbasis Ekstrak Kulit Manggis (Garcinia mangostana L.) sebagai Sensor Penurunan Kualitas Susu Sapi Akibat Kesalahan Suhu Penyimpanan (Development of Time-Temperature Indicator Based on Mangosteen Rind (Garcinia - Yayan Ika Rachmawati; Bambang Kuswandi; Nia Kristiningrum (UPT Percetakan dan Penerbitan Universitas Jember, 2016)
Anthocyanin is reddish purple pigment found abundantly in fruits, vegetables, and flowers. Time-temperature indicator (TTI) based on anthocyanin extracted from mangosteen rind was developed for monitoring quality of cow's milk, especially fresh milk stored at room temperature. TTI consists of two membranes, namely indicator membranes and acetic acid membranes. Extract of mangosteen rind and sodium hidroxide solution was also co-immobilized onto Whatman filter paper to make indicator membrane, while acetic acid solution was also separately immobilized onto filter paper obtain acetic acid membrane. Color changes as TTI's responses were monitored directly using both visual inspection and quantitative measurement via color image analysis using ImageJ software. The color changes were further correlated with cow's milk freshness parameters such as pH, smell, and number of microbial. Fresh cow's milk quality spoiled after 4 hours stored at room temperature and color changes of TTI to bright yellow occured after 4 hours of exposure at room temperature. The result shown that the TTI can be applied for monitoring quality of cow's milk stored in room temperature. Keywords: mangosteen rind, TTI, cow's milk quality